2017
DOI: 10.1590/s1677-5538.ibju.2017.0070
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pectopexy: initial experience of single center with a new technique for apical prolapse surgery

Abstract: Objective:To share our first experience with laparoscopic pectopexy, a new technique for apical prolapse surgery, and to evaluate the feasibility of this technique.Materials and Methods:Seven patients with apical prolapse underwent surgery with laparoscopic pectopexy. The lateral parts of the iliopectineal ligament were used for a bilateral mesh fixation of the descended structures. The medical records of the patients were reviewed, and the short-term clinical outcomes were analyzed.Results:The laparoscopic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Pelvic organ prolapse (POP) is a worldwide health problem, the prevalence of which ranges from 10% in younger women to 50% in postmenopausal women. Apical defect, the least frequent of all POP types, has been reported in 5%‐15% of women . DeLancey established three levels of support for proper position of the pelvic organs: Level I: uterosacral ligaments (damage: uterine/vaginal vault prolapse, enterocoele); Level II: pubocervical and rectovaginal fascia (damage: cystocele, rectocele); Level III: perineal membrane and perineal body (damage: urethrocele, perineal body defect/excessive perineal descent) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelvic organ prolapse (POP) is a worldwide health problem, the prevalence of which ranges from 10% in younger women to 50% in postmenopausal women. Apical defect, the least frequent of all POP types, has been reported in 5%‐15% of women . DeLancey established three levels of support for proper position of the pelvic organs: Level I: uterosacral ligaments (damage: uterine/vaginal vault prolapse, enterocoele); Level II: pubocervical and rectovaginal fascia (damage: cystocele, rectocele); Level III: perineal membrane and perineal body (damage: urethrocele, perineal body defect/excessive perineal descent) …”
Section: Introductionmentioning
confidence: 99%
“…Pubocervical ligaments attach to the anterior, cardinal ligaments to the lateral, and uterosacral ligaments to the posterior parts of the pericervical ring. Damage to these structures results in clinical uterine prolapse or enterocoele …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the close anatomical structures which are present at the operation field; small intestines, sigmoid colon, ureter and presacral vessels are in risk of injury. Kale et al (14) conducted a case series study and applied pectopexy to seven patients with apical prolapse and reported no intraoperative and postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
“…During the pectopexy surgery, the pectineal ligament represents a distant space from the intestines, sigmoid colon, presacral vessels, and ureter, thus they stated that the pectineal ligament maintains a safe surgical field in pectopexy surgery. Moreover, Kale et al (14) offered this technique as a feasible procedure because the surgeon uses a wide area in the pelvis and the strong nature of pectineal ligament would decrease the postoperative recurrence rates. Our study did not demonstrate the exact anatomic distance to these structures; however, our anatomic dissections revealed that the small intestines and sigmoid colon were far away from the operation field unless an adhesion was detected.…”
Section: Discussionmentioning
confidence: 99%